2013
DOI: 10.1007/s11357-013-9608-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of dementia in patients with osteoporosis: a population-based retrospective cohort analysis

Abstract: Osteoporosis is a common systemic skeletal disease that predominantly affects people older than 50 years and often co-occurs with dementia. The purpose of this study was to evaluate the risk of dementia in osteoporosis patients in Taiwan. Using data from Taiwan's National Health Insurance Research Database (NHIRD), we identified 23,941 patients with osteoporosis from 2000 to 2010 and 47,579 nonosteoporosis control patients, frequency-matched for age, sex, and index year, excluding patients with dementia at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 39 publications
4
51
1
Order By: Relevance
“…From a genetic point of view, an association of the Apo E4 allele with low BMD has been repeatedly reported, yet results are conflicting [1, 35]. In the present study, serum vitamin D levels were lower among participants who developed cognitive impairment; nevertheless, the association of low BMD with cognitive impairment was independent of vitamin levels.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…From a genetic point of view, an association of the Apo E4 allele with low BMD has been repeatedly reported, yet results are conflicting [1, 35]. In the present study, serum vitamin D levels were lower among participants who developed cognitive impairment; nevertheless, the association of low BMD with cognitive impairment was independent of vitamin levels.…”
Section: Discussioncontrasting
confidence: 54%
“…In fact, dementia has been detected in 14–20 % of older subjects; approximately 4.6 million people are diagnosed with dementia each year, with a twofold increase in the disease prevalence every 20 years [1]. By 2020, the population with a diagnosis of dementia is expected to increase to 42.3 million worldwide, and to 81.1 million by 2040 [1]. The incidence of dementia disorders increases exponentially beyond the age of 65.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found PPIs to be associated with an increased risk of dementia 2122 Osteoporosis, one of the most common indications for calcium, has also been associated with increased risk of dementia 2324 In the present study, participants in their middle age taking PPIs or calcium showed poorer cognitive performance compared to non-takers.…”
Section: Discussionmentioning
confidence: 41%
“…Although osteoporosis is a major health burden in the elderly, treatments for this disease are far from ideal. Osteoporosis and Alzheimer’s disease (AD) are common chronic degenerative disorders which are strongly associated with advanced age [1,2,3]. AD is frequently associated with fractures and reduction in bone mineral density, even at early stages of disease when patients are still active [4,5,6], indicating that AD and osteoporosis may share conserved pathogenic mechanisms.…”
Section: Introductionmentioning
confidence: 99%